2004
DOI: 10.1097/01.tp.0000128167.60172.cc
|View full text |Cite
|
Sign up to set email alerts
|

Natural History, Risk Factors, and Impact of Subclinical Rejection in Kidney Transplantation

Abstract: Histologic evidence of acute rejection in the absence of clinical suspicion resulted in significant tubulointerstitial damage to transplanted kidneys and contributed to CAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
235
3
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(252 citation statements)
references
References 24 publications
12
235
3
2
Order By: Relevance
“…More recent studies have reported on early subclinical rejection in patients who received tacrolimus, either with (10,11,13,21,22) or without (7) MMF. Jurewicz (7) reported a prevalence of subclinical rejection (that included "borderline") of 18% at 3 mo in patients who received kidneys from deceased donors and were treated with tacrolimus, azathioprine, and prednisone.…”
Section: Prevalence Of Subclinical Rejectionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent studies have reported on early subclinical rejection in patients who received tacrolimus, either with (10,11,13,21,22) or without (7) MMF. Jurewicz (7) reported a prevalence of subclinical rejection (that included "borderline") of 18% at 3 mo in patients who received kidneys from deceased donors and were treated with tacrolimus, azathioprine, and prednisone.…”
Section: Prevalence Of Subclinical Rejectionmentioning
confidence: 99%
“…Jurewicz (7) reported a prevalence of subclinical rejection (that included "borderline") of 18% at 3 mo in patients who received kidneys from deceased donors and were treated with tacrolimus, azathioprine, and prednisone. Nankivell et al (22) reported a prevalence of subclinical rejection (including borderline) of Ͼ50% at 1 mo that was virtually abolished at 3, 6, and 12 mo in patients who were on tacrolimus and MMF. Gloor et al (11) reported a similar prevalence of subclinical rejection of only 2.6% at 3 mo in patients who were on tacrolimus and MMF.…”
Section: Prevalence Of Subclinical Rejectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, early inflammation detected in protocol biopsies predicts progression of renal fibrosis and shorter renal allograft survival (248)(249)(250).…”
Section: Key Molecular Effector Systems and Therapies In Renal Fibrosismentioning
confidence: 99%
“…Such findings are common within the first 3 months of the transplant, occurring in approximately 30% of patients with stable allograft function who are receiving a cyclosporin-based regimen [13]. Although the clinical significance of subclinical rejection remains to be determined, some authors [14] suggested that it precedes the development of chronic allograft nephropathy. Thus, our two cases fit the definitions of both subclinical rejection and SRL-associated edema.…”
Section: Casementioning
confidence: 98%